Evaluating the Psychometric Properties of the Original Grit Scale Using Rasch Analysis in an Arab Adolescent Sample - Areepattamannil, S.; Khine, Myint Swe (2018)
© The Author(s) 2017. This study examined the psychometric properties of the Original Grit Scale using Rasch analysis in a sample of 777 adolescents hailing from a collectivistic society, one of the Arab states of the Persian Gulf. Results of the Rasch analysis provided support for the appropriateness of the Original Grit Scale as a measure of one of the noncognitive skills, grit, among adolescents in the Arab Gulf State. Implications of the findings are briefly discussed.